THE IMPLEMENTATION OF CRIMINAL ACT TOWARDS HATE SPEECH IN SOCIAL MEDIA - Erfan, Muhammad; Prawesthi, Wahyu; Amiq, Bahrul (jfpublisher, 2023)
Indonesia is a country that adheres to a democratic system where people are given the freedom to express their opinions. Along with globalization era, communication media are increasingly developing, such as the existence of electronic communication media that can connect people regardless of distance and place. Information technology, beside contributing to improving communication progress, technology can also be an effective means for users of social media to commit acts against the law. Cybercrime is a type of criminal activity that makes use of advances in computer technology, particularly the internet. This research examines all the regulation and law in Indonesia regarding of hate speech towards social media through normative legal research. From the research result, it found that the implementation of Hate Speech in social media networks can be determined in Article 45A Paragraph (2) jo. Article 28 Paragraph (2) of Law No, 19/2016 as Amendment to Law No. 11/2008 concerning on Electronic Information and Transactions, there does not have to be an aggrieved party or there must be an objecting party, because it is not a material offense that requires the consequences of the act.